The Effect of Providing Self-Love Education to Increase Happiness in Grade I Students of SMKS Al-Fajar - Sakti, Yenni Merdeka; Afriani, Miskah; Asrul, Asrul; Amelia, Wanna Zhirah (Journal Analytica Islamica, 2023)
Self love is a person's way of loving themselves and treating themselves well. Individuals who have self-love will increase happiness within themselves. Providing education regarding the importance of self-love is also very important, especially during the transition period between the adolescent development period and the early adulthood period. The aim of this research is to find out the effect of providing self-love education in increasing happiness in class I students at SMKS Al-Fajar. This research uses quantitative methods. The research population was 50 people who were class I students at SMKS Al-Fajar Sei Mencirim and the sample in this study was 25 people. The sampling technique used in this research was purposive sampling. The measuring instrument used is a questionnaire, namely the happiness scale questionnaire. Hypothesis testing in this research was carried out using t-test analysis. Based on the results of data analysis, it shows that using lecture, discussion and question and answer methods using video learning and Microsoft Power Point with Self Love and Happiness material obtained an average pre-test score of 124,840 and post-test of 144,280. Based on the results of hypothesis testing, the post-test t result was 6.583 and the significance value was 0.294. The significance value states that it is greater than 0.05, so it can be said that there is no significant difference. In this research, self-love has a relationship with the happiness of grade 1 students at SMKS Al-Fajar.